A high-speed printable PHA composition and preparation method thereof

By using PHA compositions with specific ratios in 3D printing materials, the problem of excessive rigidity of existing materials during printing is solved, and higher thermal deformation temperature and tensile strength are achieved, and printing speed and quality are improved.

CN119735931APending Publication Date: 2025-04-01NINGBO HOMELINK ECO ITECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411931233.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing thermoplastic polymer materials are too rigid during 3D printing, resulting in poor printing and affecting continuity.

Method used

Using a high-speed printing PHA composition, including base PHA resin, triethyl citrate, polyethylene wax, talc, antioxidants, compatibilizers, antihydrolyzers, zinc stearate and pigments, the crystallization speed and thermal deformation temperature of the composition are increased by specific mixing and processing methods.

Benefits of technology

The thermal deformation temperature and tensile strength of the printed products are significantly improved, the quality and printable speed of the print parts are enhanced, while maintaining stable performance at higher printing speeds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a high-speed printable PHA composition and a preparation method thereof, and relates to the field of thermoplastic materials. The high-speed printable PHA composition comprises the following raw materials in parts by weight: 80 parts of a basic PHA resin, 10 parts of triethyl citrate, 4 parts of polyethylene wax, 0.3 parts of an antioxidant, 1 part of talcum powder, 2 parts of maleic anhydride grafted polyethylene, 0.1 part of carbodiimide, and 0.8 parts of zinc stearate. The invention mixes triethyl citrate and polyethylene wax with the basic PHA resin, and talcum powder can help accelerate the crystallization speed, improve the heat deformation temperature of the composition and the final printed product, and adds triethyl citrate plasticizer to adjust the melt viscosity without significantly sacrificing tensile strength and elongation at break, so as to obtain a smoother printing experience and improve the effect of the printed product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thermoplastic materials, and in particular to a high-speed printable PHA composition and a preparation method thereof. Background Art

[0002] 3D printing is a type of rapid prototyping technology. It is a technology that uses digital model files as the basis, uses materials such as metals, ceramics or polymers, and uses powder, liquid or filamentous starting shapes to construct objects layer by layer through different printing methods.

[0003] At present, the printing materials of 3D printers mainly involve thermoplastic polymer materials used in fused deposition modeling. For the molding materials of fused deposition modeling, the filament-shaped printing materials on the market are too rigid and have no ductility. They are easy to bend and cannot be restored or break during the 3D printing filament supply process, resulting in uneven printing and affecting the continuity of production.

[0004] Therefore, it is necessary to provide a new high-speed printable PHA composition and a preparation method thereof to solve the above technical problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-speed printable PHA composition and a preparation method thereof.

[0006] In one aspect, the high-speed printable PHA composition provided by the present invention comprises the following raw materials in parts by weight: 80-100 parts of a basic PHA resin, 10-15 parts of a plasticizer, 4-6 parts of a polyethylene wax, 0.3-0.5 parts of an antioxidant, 1-3 parts of talc, 2-5 parts of a compatibilizer, 0.1-0.3 parts of an anti-hydrolysis agent, 0.8-2 parts of zinc stearate, and 0-5 parts of a pigment.

[0007] Furthermore, the basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:3.

[0008] Furthermore, the plasticizer is triethyl citrate or monoglyceride.

[0009] Furthermore, the compatibilizer is maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene.

[0010] Furthermore, the antioxidant comprises a primary antioxidant and a secondary antioxidant in a weight ratio of 2:1.

[0011] Furthermore, the anti-hydrolysis agent is carbodiimide.

[0012] Another aspect of the present invention provides a method for preparing a high-speed printable PHA composition, the method comprising the following steps:

[0013] S1. Raw material preparation: prepare each raw material by weight;

[0014] S2, premixing: talcum powder, compatibilizer, antioxidant, polyethylene wax, zinc stearate, anti-hydrolysis agent and pigment are mixed evenly to obtain a solid mixture;

[0015] S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and plasticizer and performing melt treatment to obtain a molten mixed material;

[0016] S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition;

[0017] S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing to obtain a finished PHA composition.

[0018] In a further method, the melt treatment in step S3 is to set a gradually increasing temperature gradient from the feed zone to the outlet zone of the twin-screw extruder for melting.

[0019] Further, in the step S5, the drying temperature is 40-60° C., the drying time is 0.5-1 h, the annealing temperature is 40-80° C., and the annealing time is 0.5-1 h.

[0020] In a further method, the temperature gradient in the melt treatment is set at 150-180°C.

[0021] Compared with the related art, the high-speed printable PHA composition and preparation method thereof provided by the present invention have the following beneficial effects:

[0022] 1. The present invention mixes triethyl citrate, polyethylene wax and basic PHA resin, and adds talcum powder to help accelerate the crystallization rate, significantly improve the heat deformation temperature of the printed product, and add triethyl citrate plasticizer to adjust the melt viscosity, which can not only effectively improve the tensile strength and elongation at break at a lower printing speed, improve the quality of the printed part, but also significantly improve the printable speed of the composition.

[0023] 2. In the present invention, polyethylene wax is added to further improve the fluidity and ductility of the melt, and a compatibilizer is added to promote good mixing between different components to avoid stratification or unevenness. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with the embodiments.

[0025] Embodiment 1

[0026] In a specific implementation process, a high-speed printable PHA composition includes the following raw materials in parts by weight: 80 parts of basic PHA resin, 10 parts of triethyl citrate, 4 parts of polyethylene wax, 0.3 parts of antioxidant, 1 part of talc, 2 parts of maleic anhydride grafted polyethylene, 0.1 parts of carbodiimide, and 0.8 parts of zinc stearate.

[0027] Furthermore, the basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:3.

[0028] Furthermore, the antioxidant comprises Irganox 1010 antioxidant and Irgafos 168 antioxidant in a weight ratio of 2:1.

[0029] A method for preparing a high-speed printable PHA composition, the method comprising the following steps:

[0030] S1. Raw material preparation: prepare each raw material by weight;

[0031] S2, premixing: talc, maleic anhydride grafted polyethylene, Irganox 1010 antioxidant, Irgafos 168 antioxidant, polyethylene wax, zinc stearate and carbodiimide are uniformly mixed to obtain a solid mixture;

[0032] S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, setting the temperature gradient from the feed zone to the outlet zone of the twin-screw extruder to 150-180° C., and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and triethyl citrate to obtain a molten mixed material;

[0033] S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition;

[0034] S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing treatment, wherein the drying temperature is 40° C., the drying time is 0.5 h, and the annealing temperature is 40° C., the annealing time is 0.5 h, to obtain a finished PHA composition.

[0035] Embodiment 2

[0036] In a specific implementation process, the high-speed printable PHA composition provided by the present invention includes the following raw materials in parts by weight: 90 parts of basic PHA resin, 12 parts of triethyl citrate, 5 parts of polyethylene wax, 0.4 parts of antioxidant, 2 parts of talc, 3 parts of maleic anhydride grafted polyethylene, 0.2 parts of carbodiimide, 1 part of zinc stearate, and 3 parts of pigment.

[0037] Furthermore, the basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:3.

[0038] Furthermore, the antioxidant comprises Irganox 1010 antioxidant and Irgafos 168 antioxidant in a weight ratio of 2:1.

[0039] A method for preparing a high-speed printable PHA composition, the method comprising the following steps:

[0040] S1. Raw material preparation: prepare each raw material by weight;

[0041] S2, premixing: talcum powder, maleic anhydride grafted polyethylene, Irganox 1010 antioxidant, Irgafos 168 antioxidant, polyethylene wax, zinc stearate, carbodiimide and pigment are uniformly mixed to obtain a solid mixture;

[0042] S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, setting the temperature gradient from the feed zone to the outlet zone of the twin-screw extruder to 150-180° C., and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and triethyl citrate to obtain a molten mixed material;

[0043] S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition;

[0044] S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing treatment, wherein the drying temperature is 50° C., the drying time is 0.8 h, the annealing temperature is 60° C., and the annealing time is 0.8 h, to obtain a finished PHA composition.

[0045] Embodiment 3

[0046] In a specific implementation process, a high-speed printable PHA composition includes the following raw materials in parts by weight: 100 parts of basic PHA resin, 15 parts of triethyl citrate, 6 parts of polyethylene wax, 0.5 parts of antioxidant, 3 parts of talc, 5 parts of maleic anhydride grafted polyethylene, 0.3 parts of carbodiimide, 2 parts of zinc stearate, and 5 parts of pigment.

[0047] Furthermore, the basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:3.

[0048] Furthermore, the antioxidant comprises Irganox 1010 antioxidant and Irgafos 168 antioxidant in a weight ratio of 2:1.

[0049] A method for preparing a high-speed printable PHA composition, the method comprising the following steps:

[0050] S1. Raw material preparation: prepare each raw material by weight;

[0051] S2, premixing: talcum powder, maleic anhydride grafted polyethylene, Irganox 1010 antioxidant, Irgafos 168 antioxidant, polyethylene wax, zinc stearate, carbodiimide and pigment are uniformly mixed to obtain a solid mixture;

[0052] S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, setting the temperature gradient from the feed zone to the outlet zone of the twin-screw extruder to 150-180° C., and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and triethyl citrate to obtain a molten mixed material;

[0053] S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition;

[0054] S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing treatment, wherein the drying temperature is 60° C., the drying time is 1 hour, and the annealing temperature is 80° C., the annealing time is 1 hour, to obtain a finished PHA composition.

[0055] Embodiment 4

[0056] In a specific implementation process, a high-speed printable PHA composition includes the following raw materials in parts by weight: 80 parts of basic PHA resin, 10 parts of monoglyceride, 4 parts of polyethylene wax, 0.3 parts of antioxidant, 1 part of talc, 2 parts of maleic anhydride grafted polypropylene, 0.1 parts of carbodiimide, and 0.8 parts of zinc stearate.

[0057] Furthermore, the basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:3.

[0058] Furthermore, the antioxidant comprises Irganox 1010 antioxidant and Irgafos 168 antioxidant in a weight ratio of 2:1.

[0059] A method for preparing a high-speed printable PHA composition, the method comprising the following steps:

[0060] S1. Raw material preparation: prepare each raw material by weight;

[0061] S2, premixing: talc, maleic anhydride grafted polypropylene, Irganox 1010 antioxidant, Irgafos 168 antioxidant, polyethylene wax, zinc stearate and carbodiimide are uniformly mixed to obtain a solid mixture;

[0062] S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, setting the temperature gradient from the feed zone to the outlet zone of the twin-screw extruder to 150-180° C., and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and monoglyceride to obtain a molten mixed material;

[0063] S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition;

[0064] S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing treatment, wherein the drying temperature is 40° C., the drying time is 0.5 h, and the annealing temperature is 40° C., the annealing time is 0.5 h, to obtain a finished PHA composition.

[0065] Embodiment 5

[0066] In a specific implementation process, a high-speed printable PHA composition includes the following raw materials in parts by weight: 90 parts of basic PHA resin, 12 parts of monoglyceride, 5 parts of polyethylene wax, 0.4 parts of antioxidant, 2 parts of talc, 3 parts of maleic anhydride grafted polypropylene, 0.2 parts of carbodiimide, 1 part of zinc stearate, and 3 parts of pigment.

[0067] Furthermore, the basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:3.

[0068] Furthermore, the antioxidant comprises Irganox 1010 antioxidant and Irgafos 168 antioxidant in a weight ratio of 2:1.

[0069] A method for preparing a high-speed printable PHA composition, the method comprising the following steps:

[0070] S1. Raw material preparation: prepare each raw material by weight;

[0071] S2, premixing: talcum powder, maleic anhydride grafted polypropylene, Irganox 1010 antioxidant, Irgafos 168 antioxidant, polyethylene wax, zinc stearate, carbodiimide and pigment are uniformly mixed to obtain a solid mixture;

[0072] S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, setting the temperature gradient from the feed zone to the outlet zone of the twin-screw extruder to 150-180° C., and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and monoglyceride to obtain a molten mixed material;

[0073] S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition;

[0074] S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing treatment, wherein the drying temperature is 50° C., the drying time is 0.8 h, the annealing temperature is 60° C., and the annealing time is 0.8 h, to obtain a finished PHA composition.

[0075] Embodiment 6

[0076] In a specific implementation process, a high-speed printable PHA composition includes the following raw materials in parts by weight: 100 parts of basic PHA resin, 15 parts of monoglyceride, 6 parts of polyethylene wax, 0.5 parts of antioxidant, 3 parts of talc, 5 parts of maleic anhydride grafted polypropylene, 0.3 parts of carbodiimide, 2 parts of zinc stearate, and 5 parts of pigment.

[0077] Furthermore, the basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:3.

[0078] Furthermore, the antioxidant comprises Irganox 1010 antioxidant and Irgafos 168 antioxidant in a weight ratio of 2:1.

[0079] A method for preparing a high-speed printable PHA composition, the method comprising the following steps:

[0080] S1. Raw material preparation: prepare each raw material by weight;

[0081] S2, premixing: talcum powder, maleic anhydride grafted polypropylene, Irganox 1010 antioxidant, Irgafos 168 antioxidant, polyethylene wax, zinc stearate, carbodiimide and pigment are uniformly mixed to obtain a solid mixture;

[0082] S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, setting the temperature gradient from the feed zone to the outlet zone of the twin-screw extruder to 150-180° C., and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and monoglyceride to obtain a molten mixed material;

[0083] S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition;

[0084] S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing treatment, wherein the drying temperature is 60° C., the drying time is 1 hour, and the annealing temperature is 80° C., the annealing time is 1 hour, to obtain a finished PHA composition.

[0085] Comparative Example 1

[0086] A printing resin composition comprises the following raw materials in parts by weight: 80 parts of basic PHA resin, 10 parts of triethyl citrate, 4 parts of polyethylene wax, 0.3 parts of antioxidant, 2 parts of maleic anhydride grafted polyethylene, 0.1 parts of carbodiimide, 0.8 parts of zinc stearate and 1 part of pigment.

[0087] Comparative Example 2

[0088] A printing resin composition comprises the following raw materials in parts by weight: 80 parts of basic PHA resin, 4 parts of polyethylene wax, 0.3 parts of antioxidant, 2 parts of maleic anhydride grafted polyethylene, 0.1 parts of carbodiimide, 0.8 parts of zinc stearate and 1 part of pigment.

[0089] Comparative Example 3

[0090] A printing resin composition comprises the following raw materials in parts by weight: 80 parts of basic PHA resin, 10 parts of triethyl citrate, 0.3 parts of antioxidant, 2 parts of maleic anhydride grafted polyethylene, 0.1 parts of carbodiimide, 0.8 parts of zinc stearate and 1 part of pigment.

[0091] Comparative Example 4

[0092] A printing resin composition comprises the following raw materials in parts by weight: 80 parts of basic PHA resin, 10 parts of triethyl citrate, 4 parts of polyethylene wax, 0.3 parts of antioxidant, 1 part of talcum powder, 0.1 parts of carbodiimide, 0.8 parts of zinc stearate and 1 part of pigment.

[0093] Experiment 1

[0094] According to the ingredients and preparation methods of Examples 1 to 6, PHA compositions were prepared and extruded and rolled with the printing resin compositions of Comparative Examples 1 to 4 through a 3D printing wire machine to obtain 3D printing wires, which were then printed into ASTM D638 standard tensile specimens and ASTM D648 standard thermal deformation specimens at speeds of 200 mm / s and 400 mm / s using a fused deposition 3D printer. Performance tests were performed on the specimens, and specific comparison results are shown in the following table:

[0095]

[0096] It can be seen from the above table that by mixing triethyl citrate, polyethylene wax and basic PHA resin, talcum powder can help accelerate the crystallization rate and significantly increase the heat deformation temperature of the printed product. Adding triethyl citrate plasticizer to adjust the melt viscosity can not only effectively improve the tensile strength and elongation at break at a lower printing speed, and improve the quality of the printed part: it can also significantly increase the printable speed of the composition: more importantly, at a higher printing speed, the performance of the printed part does not show a significant decrease.

[0097] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any mark in the claims should not be regarded as limiting the claims involved.

[0098] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-speed printable PHA composition, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of basic PHA resin, 10-15 parts of plasticizer, 4-6 parts of polyethylene wax, 0.3-0.5 parts of antioxidant, 1-3 parts of talc, 2-5 parts of compatibilizer, 0.1-0.3 parts of anti-hydrolysis agent, 0.8-2 parts of zinc stearate and 0-5 parts of pigment.

2. The high-speed printable PHA composition according to claim 1, characterized in that: The basic PHA resin includes PHB resin and PHBV resin in a weight ratio of 7:

3.

3. The high-speed printable PHA composition according to claim 1, characterized in that: The plasticizer is triethyl citrate or monoglyceride.

4. The high-speed printable PHA composition according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene.

5. The high-speed printable PHA composition according to claim 1, characterized in that: The antioxidant comprises a primary antioxidant and an auxiliary antioxidant in a weight ratio of 2:

1.

6. The high-speed printable PHA composition according to claim 1, characterized in that: The anti-hydrolysis agent is carbodiimide.

7. A method for preparing a high-speed printable PHA composition as claimed in any one of claims 1 to 6, characterized in that: The method comprises the following steps: S1. Raw material preparation: prepare each raw material by weight; S2, premixing: talcum powder, compatibilizer, antioxidant, polyethylene wax, zinc stearate, anti-hydrolysis agent and pigment are mixed evenly to obtain a solid mixture; S3, main mixing: adding most of the basic PHA resin into the twin-screw extruder, and then gradually adding the solid mixed material premixed in step S2 for mixing. During the mixing process, gradually adding the remaining basic PHA resin and plasticizer and performing melt treatment to obtain a molten mixed material; S4, granulation: the molten mixture is extruded through a die head and rapidly cooled in water, and the cooled strip material is cut into small particles using a pelletizer to obtain a granulated PHA composition; S5. Post-treatment: The granulated PHA composition is placed in a drying oven for drying and annealing to obtain a finished PHA composition.

8. The high-speed printable PHA composition and preparation method thereof according to claim 7, characterized in that: The melting treatment in step S3 is to set a gradually increasing temperature gradient from the feed zone to the outlet zone of the twin-screw extruder for melting.

9. The high-speed printable PHA composition and the preparation method thereof according to claim 7, characterized in that: In the step S5, the drying temperature is 40-60° C., the drying time is 0.5-1 h, the annealing temperature is 40-80° C., and the annealing time is 0.5-1 h.

10. The high-speed printable PHA composition and the preparation method thereof according to claim 8, characterized in that: The temperature gradient in the melt treatment is set at 150-180°C.